Brazilian Import Demand of Dairy Products with Emphasis in the Mercosul Context - García Arancibia, Rodrigo (2020)
Brazil is the largest milk producer in South America, with an increasing trend in the last 20 years which allowed the country to start exporting some output. However, it has not become self-reliant and continues to be a major importer in the region, the most relevant partner for Argentina and Uruguay in Mercosul. In this paper, the Brazilian import demand of dairy products is estimated by using a source differentiated demand system framework that is derived from consumer theory. This model takes into account the countries of origin (i.e., Argentina, Uruguay and other grouped competitors) and various dairy aggregated items that compete in the Brazilian market. The expenditure elastici-ties, and the own and cross-price elasticities are computed with the estimated parame-ters of the demand system. Interpretation of results follows as well as some conclusions, including the need of further studies and usefulness of this type of research.